Rodríguez Gutiérrez, M. (2023). Las poetas cubanas: lo cubano, lo contemporáneo. Peter Lang. - Rosario Pérez Cabaña (América sin Nombre)
Reseña de Rosario Pérez Cabaña: Rodríguez Gutiérrez, M. (2023). Las poetas cubanas: lo cubano, lo contemporáneo. New York: Peter Lang. 217 pp. ISBN 978-1-4331-8814-5.